Aplikasi Theory Middle Range “The Health Promotion Model of Pender” Terhadap Faktor-Faktor yang Mempengaruhi Tingkat Kecemasan Pada Remaja Putri di Masa Pubertas: Literature Riview - Dumar, Bergita; Sri Mulyani; Ida Wahyuni; Mery Eka Yaya Fujianti (Indonesian Health Science Journal, 2025)
Background: Anxiety is often experienced by adolescents due to various changes that occur both biologically, psychologically, and socially, which can affect their emotional state. Objective: This study aims to discuss the application of the middlerange theory "Health Promotion of Pender" to factors that can influence anxiety levels in adolescents during puberty. Method: This literature review uses articles published in the last 8 years, namely from 2017 to 2024 with a total number of articles of 1,544. Keyword determination is done using the PICO format according to the topic of the assignment. Article searches are carried out through the Proquest, Sciencedirect, and Google Scholar databases, following the inclusion and exclusion criteria that have been determined. The article identification process uses the PRISMA Flowchart diagram so that the total number of articles that match the topic is 5 articles. Results: from the search results, a number of articles were found that were relevant to the topic of this literature review which resulted in themes related to the application of the middlerange theory "Health Promotional Pender" to factors that can influence anxiety in adolescents during puberty, where the factors that most influence anxiety are psychological factors such as peer pressure, social media and negative self image. Conclusion: The results of this literature review indicate that factors that can trigger anxiety in adolescents include peer pressure (environment), social media, and negative self-image. Success in modifying behavior and improving health behavior in adolescents in dealing with changes during puberty is one form of the role and function of the Pender health promotion model (PHM). The recommendation for the next author is to see to what extent the Pender health promotion model (PHM) can be integrated by schools.